HYPERTENSION IN PRIMARY HYPERPARATHYROIDISM: A CASE REPORT OF ECTOPIC PARATHYROID ADENOMA - Dimitrovska, Irena; Vejseli, Ron; Volkanovska ilijevska, Cvetanka; Arbutina, Suzana; Trajkovska, Tina; Kuzmanoska, Ivana; Bojadzioska, Maja; Asani, Elldar; Taseva, Latinka (Македонско лекарско друштво = Macedonian medical association, 2024)
Primary hyperparathyroidism is a condition characteri- zed by excessive production of parathyroid hormone, often caused by an adenoma or hyperplasia of the parathyroid gland. One of the rare presentations of primary hyperparathyroidism is the development of an ectopic parathyroid adenoma, which can be challen- ging to diagnose and localize. Hypertension is observed seen in many cases of primary hyperparathyroidism (PHPT), although the exact mechanism is yet unclear. This paper aims to provide a comprehensive review of the current understanding of primary hyperparathy- roidism, with a focus on the presentation of ectopic adenomas and the relationship between primary hyper- parathyroidism and resistant hypertension. While most parathyroid adenomas are located in the normal ana- tomical position of the parathyroid glands, a small percentage (approximately 2-5%) can occur in ectopic locations, such as the thyroid gland, carotid sheath, or mediastinum. The atypical location of ectopic parathy- roid adenomas can make them more difficult to iden- tify and remove surgically, which can be difficult diag- nostic challenge. The prevalence of primary hyperpa- rathyroidism has been estimated to be around 0.1-0.4% in the general population, with a higher incidence in postmenopausal women. The imaging tests consist mainly of an initial 99mTc- sestamibi SPECT/CT. Sensitivity and specificity of sestamibi scans are between 73%-80%, respectively. Clinical sensitivity is increased to 96% when sestamibi scans are combined with ultrasound
ХИПЕРТЕНЗИЈА ПРИ ПРИМАРЕН ХИПЕРПАРАТИРЕОИДИЗАМ: СЛУЧАЈ НА ЕКТОПИЧНА ПАРАТИРЕОИДНА АДЕНОМА